Energy deficit does not affect immune responses of experimentally infected pacu (Piaractus mesopotamicus) - Gimbo, Rodrigo Y. [UNESP]; Favero, Gisele C. [UNESP]; Franco Montoya, Luz N. [UNESP]; Urbinati, Elisabeth C. [UNESP] (Elsevier B.V., 2015)
We investigated if the energy deficit following a 30-day starvation period could affect the ability of fish to mount immune responses after experimental exposure to Aeromonas hydrophila. Fish were submitted to two feeding strategies during 30 days: starvation and continuously feeding. Fish were then sampled to allow for the assessment of baseline metabolic and immune system indicators, were next intraperitonially inoculated with A. hydrophila, and finally were sampled at 3 and 24 h after the challenge. The respiratory activity of leukocytes was lower in starved fish at baseline, increasing after bacterial inoculation to levels similar to those seen among fed fish. Levels of serum lysozyme were higher in starved fish at baseline. The same response profile was observed 3 h after inoculation, but among fed fish, these levels increased to values similar to those of starved fish 24 h after infection. Among starved fish, lysozyme concentration did not change over the course of the experiment. The serum ACH activity was lower in starved fish at baseline and increased after bacterial inoculation in both fish groups. Baseline levels of blood glucose of starved fish were lower than those of fed fish and increased 3 h after bacterial inoculation in both fish groups, decreasing in both groups at 24 h after inoculation. Baseline liver glycogen levels were similar in both fish groups and higher than at 3 and 24 h after inoculation. Three hours after bacterial inoculation, liver glycogen was less reduced in fed fish. Baseline levels of blood triglycerides were lower in starved fish and the profile remained unchanged 3 h after inoculation. There was a gradual decrease in fed fish, and the levels of starved fish remained unchanged throughout the observation period. Blood glycerol levels at baseline were higher in starved fish than in fed fish and remained unaltered at 3 h after inoculation. However those levels increased at 24 h. In fed fish there was a gradual increase of glycerol levels up to 24 h after bacterial inoculation. Baseline liver lipid levels of starved fish were lower and this difference in the response profile remained unchanged 3 and 24 h after inoculation. The liver lipid levels of starved fish decreased after inoculation, and remained unchanged in fed fish. As observed in liver lipid, muscle lipid levels of starved fish were lower than in fed fish, throughout the experiment. Starved fish levels remained unchanged: however fed fish levels decreased 24 h after bacterial inoculation. Levels of cortisol were higher in starved fish at baseline and increased in both fish groups 3 h after bacterial inoculation, reaching intermediary levels 24 h after inoculation. Our results show that in pacu, although mounting an immune response triggered after bacterial exposure is an energy-expensive process, fish under energetic deficit status were able to display protection against infection. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Innate immune responses; Energy deficit; Starvation; Pacu